The Effect of Granisetron on Sensory Detection and Pain Thresholds in Facial Skin of Healthy Young Males - Ernberg, Malin; Wieslander Fältmars, Anna; Hajizadeh Kopayeh, Milad; Arzt Wallén, Sofia; Cankalp, Therese; Christidis, Nikolaos (Frontiers in Neurology, 2020)
Background: The specific serotonin type 3 (5-HT3)-receptor antagonist granisetron effectively reduces clinical as well as experimental muscle pain and hyperalgesia and with a duration that exceeds that of lidocaine. Hence, it may be an alternative to lidocaine as a local anesthetic. There are also some indications that granisetron in addition to 5-HT3 receptors blocks sodium channels. Thus, the local anesthetic effect by granisetron may resemble that of lidocaine, but this has not been tested. The aim of this study was therefore to compare the effect by granisetron has on facial skin-sensitivity to the effect of lidocaine and isotonic saline. Methods: This was a randomized, controlled and double-blind study, in which 1 ml of either granisetron (test-substance), lidocaine (positive control) and isotonic saline (negative control) were injected into the skin over the masseter muscle at three different occasions in eighteen healthy males (27.25.8 years old). Skin detection thresholds and pain thresholds for thermal stimuli as well as mechanical detection thresholds and sensitivity to a painful mechanical (pin-prick) stimulus were assessed before (baseline) and 5, 20, 40, and 60 min after injection. The quality and area of subjective sensory change over the cheek was assessed 20 min after injection. Results: All substances increased the mechanical detection threshold (granisetron: p=0.011; lidocaine: p=0.016; saline: p=0.031). Both granisetron and lidocaine, but not isotonic saline, increased the heat detection thresholds (p<0.001 and p<0.02, respectively), but not the cold detection thresholds. Granisetron and lidocaine also reduced pinprick pain (p=0.001 for each comparison). There were no significant differences between granisetron and lidocaine for any of these variables. There was no effect on thermal pain thresholds for any substance. Conclusion: The similar analgesic patterns on mechanical sensory and pain thresholds as well as thermal sensory thresholds over the facial skin by subcutaneous injection of granisetron and lidocaine shown in this study and the absence of paresthesia, in combination with the reduced pain intensity and pressure pain sensitivity shown in previous studies, indicate that granisetron might be a novel candidate as a local anesthetics.